Reminiscences. - Wing, Michael (Software engineering notes.)
My favorite column in ACM publications is the "Reminiscences on Influential Papers" in the SIGMOD Record. I don't know of anything else like it, anywhere. Each issue contains a handful of short essays (usually 2 or 3 long paragraphs), explaining why one research paper or another made an impression. Usually, the cited paper influenced the author's Ph.D. thesis or subsequent research.